Application of comparative genomic hybridization and fluorescence in situ hybridization on human glioma cell lines treated with bis[S-methyl-β-N-(2-furylmethylketone) dithiocarbazato] cadmium(II) - Bakar, Suhaili Abu; Rosli, Rozita; Chong, Pei Pei; Rahman, Sabariah Abdul; Awidat, Shaban K.; Badri, Karen A. (Penerbit Universiti Sains Malaysia, 2004)
Gliomas are the most common primary tumors which arise from cells of the brain itself rather than metastazing to the brain from another location in the body. It can be slow growing (low grade, grades 1 and 2) or rapidly growing (high grade, grades 3 and 4). For instance, diffuse and fibrillary astrocytomas are divided histopathologically into three grades of malignancy: World Health Organization (WHO) grade II astrocytomas, WHO grade III anaplastic astrocytoma and WHO grade IV glioblastoma multiforme (GBM) (Otto, 2001).